Profil Kadar Kolagen Kulit dan Tulang Tikus Wistar pada Berbagai Umur yang Mendapat Perlakuan Stres Oksidatif Hiperkolesterolemia dan Oleoresin Kulit Batang Kayu Manis (Cinnamomum sp) - Sunarno, Sunarno; Isdadiyanto, Sri (Bioma : Berkala Ilmiah Biologi, 2010)
Oleoresin cinnamon bark belonging to the phenolic compounds that are known to have potential as antioxidants. On the basis of the potential of these compounds may be used to prevent or repair tissue damage, whether caused by the factors of age and condition of oxidative stress hypercholesterolemia. This study aimed to obtain skin and bone collagen profile of Wistar rats at various ages after oxidative stress treated hypercholesterolemia and oleoresin from the bark of cinnamon (Cinnamomum sp). This study used 54 male Wistar rats with body weight (200 Â± 5 g), which are grouped into six treatment groups combined with the three age groups of mice that is three, six or nine months with three replications. Each group received treatment oleoresin and hypercholesterolemia. Giving oral oleoresin conducted on rats given oral way during the 7 days with a dose of 12 rats mg/200-gr bw / day. Hypercholesterolemic rats was conducted by feeding cholesterol content within 1% during the two months. The results showed that the profile of skin and bone collagen content of the highest found on threemonth old rats treated with oleoresin, oleoresin hypercholesterolemia and given again (P6, 2), namely 57.44 tg / mg and 33.47 tg / mg, while the profile of skin and bone collagen content of the lowest found in rats aged 9 months to get treatment without treatment of hypercholesterolemia oleoresin (P2, 9), namely 28.26 tg / mg and 10.65 tg / mg. From this research can be concluded that the condition of hypercholesterolemia and duration of the aging effect on skin collagen levels decrease and bone, and vice versa oleoresin at the age of young rats that received the treatment of oxidative stress could repair or prevent hypercholesterolemia decreased content of skin collagen and bone. In general, the rats are treated oleoresin and young age profile of the collagen content of skin and bones better compared with rats that do not get treatment in conditions of oxidative stress oleoresin hypercholesterolemia.